Characterization of Cyclic N‐Acyliminium Ions by Infrared Ion Spectroscopy. Issue 9 (29th December 2021) - Merx, Jona; Houthuijs, Kas J.; Elferink, Hidde; Witlox, Eva; Mecinović, Jasmin; Oomens, Jos; Martens, Jonathan; Boltje, Thomas J.; Rutjes, Floris P. J. T.
Abstract: N‐ Acyliminium ions are highly reactive intermediates that are important for creating CC‐bonds adjacent to nitrogen atoms. Here we report the characterization of cyclic N ‐acyliminium ions in the gas phase, generated by collision induced dissociation tandem mass spectrometry followed by infrared ion spectroscopy using the FELIX infrared free electron laser. Comparison of DFT calculated spectra with the experimentally observed IR spectra provided valuable insights in the conformations of the N ‐acyliminium ions. Abstract : N‐ Acyliminium ions (NAIs) are highly reactive intermediates that are important for the construction of CC‐bonds adjacent to nitrogen atoms. These species have been characterized for the first time in the gas phase by collision induced dissociation tandem mass spectrometry followed by infrared ion spectroscopy (IRIS), which has led to new structural information that can be invoked to explain the diastereoselectivity of reactions involving these cationic intermediates.